Behaviour of Freelance Tour Guides in Promoting Ijen Crater Packages to French Tourists - I Gusti Putu Bagus Sasrawan Mananda; I Wayan Kartimin (Journal of Tourism and Economic, 2024)
This study aims to identify the behavior of French-speaking freelance tour guides in promoting tour packages to Ijen Crater, Banyuwangi, and measure the effectiveness of the digital marketing strategies used. The research methodology employs a descriptive qualitative approach with primary data sources consisting of in-depth interviews with 5 freelance tour guides and 5 French tourists. The results indicate that freelance tour guides specialize in adventure activities and possess deep cultural knowledge. French tourists are attracted to the "Blue Fire" phenomenon at Ijen Crater, as well as cultural experiences and outdoor activities. Effective digital marketing significantly impacts increasing tourist interest and visits. However, technical constraints and limited knowledge of digital marketing pose major challenges. This study provides significant contributions to the development of more effective and targeted tourism marketing strategies.